The Political Thought of Mawdudi as a Template for Democratic Sustainability in Nigeria - Rafiu Ibrahim Adebayo (Al-Jami'ah Research Centre, 2016)
The inseparability of religion and politics is demonstrated in the involvement of prominent ulama (religious scholars) in politics directly or indirectly. Being an important stakeholder in politics, such scholars have been raising their voices on political matters and influencing political decisions in their respective countries. In some cases, such religious scholars performed oppositional role with a view to forcing the ruling government to check their actions which were contradictory to the dictate of their religion. The Islamic revolution in Iran is a living testimony to the fact that religious scholars are relevant to effect new sociological and religio-political paradigms for their countries. It is on this basis that this paper shall explore the political thought of a seasoned reforming Mogul whose thought is significant to democratic sustenance in Nigeria, Maulana Abul A’la Mawdudi (1903 -1979). This sage enunciated some political principles which if strictly studied and adhered to, will help in no small measure in ensuring sustainable democratic governance whose leadership will not regret leading its people and the populace will not eventually curse such a leader. [Agama dan politik dalam banyak hal tidak dapat dipisahkan. Hal ini ditunjukkan antara lain oleh keterlibatan ulama dalam politik, langsung atau tidak. Menjadi bagian dari sistem politik, ulama dapat menyuarakan pandangan mereka dan mempengaruhi keputusan politik di negara masing-masing. Dalam beberapa kasus, para ulama juga melakukan oposisi untuk memaksa pemerintah melihat kebijakan yang bertentangan dengan ajaran agama. Revolusi Islam di Iran adalah contoh nyata dengan fakta bahwa ulama memiliki peran yang erat terkait dengan paradigma sosiologis dan religio-politik baru bagi negara. Makalah ini akan mengeksplorasi pandangan Maulana Abul A’la Maududi (1903 -1979), tokoh reformist yang pemikirannya sangat penting untuk pengembangan demokrasi di Nigeria. Beberapa prinsip politik akan membantu dalam memastikan pemerintahan yang demokratis berkelanjutan, jika dipelajari dan diikuti dengan benar.]